Anxiety, insomnia, and depression during COVID-19 lockdown in elite individual and team sport athletes - Salles, J. I.; Silva, C.; Wolff, A.; Orwert, L.; Ribeiro, P.; Velasques, B.; Morrissey, D. (Psicologia: Reflexao e Critica)
Purpose: Pandemic-induced lockdowns disrupted sport training and competition. We aimed to identify the impact on the mental health of high-level athletes and clarify whether the effects differ for team-based and individual athletes.